Public Perceptions and Sentiments on Sexual Violence against Women by Educators and Healthcare Providers - Indah Sari, Rizky Aulia; Bernardino, Sinta; Indriani, Ika Lutfiana; Ananda, Jennita Erly; Hana, Adinda Aufa; Setyasyuti, Yuanita; Maulina, Novaria (Martabat: Jurnal Perempuan dan Anak, 2025)
This study investigates public responses and sentiments on social media concerning two high-profile cases of sexual violence involving authoritative figures: a Professor at Universitas Gadjah Mada (UGM) and a Specialist Medical Education Program (PPDS) physician at Hasan Sadikin Hospital (RSHS). Employing a descriptive qualitative design and utilizing the Brand24 digital analytics tool, the research examines the dynamics of online public discourse between April and May 2025. The study seeks to elucidate how public opinion is constructed in cases of sexual violence perpetrated by individuals with structural authority, and how digital expressions of support reflect shifting societal perspectives toward victims and perpetrators. Particular attention is given to the declining prevalence of victim blaming and the emergence of greater empathy and solidarity with victims, as well as the function of social media as a platform for advocacy in confronting psychological, legal, and social barriers. The findings demonstrate a predominance of neutral sentiments (87%), alongside a notable increase in negative sentiments (11.6%), which signify public discontent with institutional responses. The study underscores the dual role of social media as both a communicative arena and a mechanism of social control that contributes to cultural transformation in the understanding of sexual violence.